2013
DOI: 10.1101/gr.147991.112
|View full text |Cite
|
Sign up to set email alerts
|

The complex SNP and CNV genetic architecture of the increased risk of congenital heart defects in Down syndrome

Abstract: Congenital heart defect (CHD) occurs in 40% of Down syndrome (DS) cases. While carrying three copies of chromosome 21 increases the risk for CHD, trisomy 21 itself is not sufficient to cause CHD. Thus, additional genetic variation and/or environmental factors could contribute to the CHD risk. Here we report genomic variations that in concert with trisomy 21, determine the risk for CHD in DS. This case-control GWAS includes 187 DS with CHD (AVSD = 69, ASD = 53, VSD = 65) as cases, and 151 DS without CHD as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 56 publications
0
70
4
1
Order By: Relevance
“…Some authors suggest that the presence of certain variants in specific genes could be the underlying cause for CHD in this population [5,36]. Others suggest a correlation with the presence of single nucleotides polymorphism (SNPs) and Copy Number Variations (CNVs) [18]. And there are also ethnical genetic differences, which could play a role in the different incidence of CHD among these patients [20,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors suggest that the presence of certain variants in specific genes could be the underlying cause for CHD in this population [5,36]. Others suggest a correlation with the presence of single nucleotides polymorphism (SNPs) and Copy Number Variations (CNVs) [18]. And there are also ethnical genetic differences, which could play a role in the different incidence of CHD among these patients [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of these defects varies among studies [8][9][10][11][12][13][14]. This could reflect inherent characteristics of the studied populations, such a higher frequency of genetic variances that predispose to the presence of AVSD [5,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Replication study of Sailani et al (2013) Two common CNVs were found to be associated with DS+AVSD in the study by Sailani et al (2013). To replicate these findings, we used the identical NanoString probes in 96 cases and controls from our DS cohort.…”
Section: Cnv Callingmentioning
confidence: 99%
“…Controls (DS+NH) are individuals with Down syndrome without a congenital heart defect. (Sailani et al 2013). CNV1 at chr21: 43,193,374-43,198,244 (hg19) was observed as a deletion in 18% of the 55 cases with DS+AVSD and 0% of the 53 DS+NH controls, and as a duplication in 7% of cases and 0% in controls.…”
Section: Replication Of Previous Findings Of Common Cnvs Associated Wmentioning
confidence: 99%
“…Congenital heart defect (CHD) occurs in approximately 40% of the DS patients (Sailani et al, 2013). The relatively higher infant mortality rate in DS patients has been largely attributed to their having a higher incidence of CHD (Weijerman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%